2021
DOI: 10.1186/s12882-021-02436-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic anticoagulation is not associated with a reduced risk of acute kidney injury in hospitalised Covid-19 patients

Abstract: Background Coronavirus-19 (COVID-19) has been declared a global pandemic by the World Health Organisation. Severe disease typically presents with respiratory failure but Acute Kidney Injury (AKI) and a hypercoagulable state can also occur. Early reports suggest that thrombosis may be linked with AKI. We studied the development of AKI and outcomes of patients with COVID-19 taking chronic anticoagulation therapy. Methods Electronic records were revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
(63 reference statements)
0
4
0
6
Order By: Relevance
“…Foram selecionados 46 estudos para a leitura exploratória e realizado a seleção de 44 artigos para a amostra final, pois atendiam aos critérios de elegibilidade conforme fluxograma (Figura 1). Todos os estudos incluídos foram publicados em língua inglesa, entre 2020 e 2022, desenvolvidos na América do Sul (16)(17)(18)(19) e América do Norte, (20)(21)(22)(23)(24)(25)(26)(27) Ásia, (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) Europa, (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) África (54) e Oriente Médio. (55)(56)(57)(58) O país com maior número de publicações sobre LRA associada à COVID-19 foi a China, contemplando 27,3% (n = 12) dos artigos.…”
Section: Resultsunclassified
“…Foram selecionados 46 estudos para a leitura exploratória e realizado a seleção de 44 artigos para a amostra final, pois atendiam aos critérios de elegibilidade conforme fluxograma (Figura 1). Todos os estudos incluídos foram publicados em língua inglesa, entre 2020 e 2022, desenvolvidos na América do Sul (16)(17)(18)(19) e América do Norte, (20)(21)(22)(23)(24)(25)(26)(27) Ásia, (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42) Europa, (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53) África (54) e Oriente Médio. (55)(56)(57)(58) O país com maior número de publicações sobre LRA associada à COVID-19 foi a China, contemplando 27,3% (n = 12) dos artigos.…”
Section: Resultsunclassified
“…In addition, Paranjpe et al showed longer duration of AC treatment reduced the risk of in-hospital mortality (aHR of 0.86 per day; 95% CI: 0.82 – 0.89; p < 0.001) [ 38 ]. On the other hand, AC was not shown to reduce the incidence or severity of MSOC such as acute kidney injury [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the data regarding the role of chronic anticoagulation in outcomes of COVID-19 has since remained conflicting. Parker et al reported reduced rates of mechanical ventilation (8.5% vs 17.4%) in chronically anticoagulated patients with COVID-19 but a higher (40.2% vs 30%) mortality rate [ 13 ]. On the other hand, Tremblay et al demonstrated no mortality benefit in a propensity matched cohort of 241 patients receiving anticoagulation prior to COVID-19 infection [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, hypertension is a recognized risk factor for renal function impairment and AKI in COVID-19 and the most common comorbidity in our study, which is supported by the literature. 24 - 26 Parker et al, 25 who aimed to investigate a possible effect of continuous anticoagulant therapy before hospitalization on the prevention of AKI, found the risk factors for AKI to be CKD, hypertension, and male sex. Our study went further and showed preexisting hypertension to be a risk factor for not only CA-AKI but also HA-AKI.…”
Section: Discussionmentioning
confidence: 99%